PERAN DAN ARTI PENTING PERJANJIAN LISENSI DALAM MELINDUNGI MEREK TERKENAL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Well-known marks are trademarks that are registered and advertised in numerous jurisdictions and media. Consumers trust them as they have high quality assurance. However, well-known marks are frequently violated, which not only injures trademark owners, but also harms the state. Therefore, management of well-known marks through licensing agreement is needed.